Atividade imunomoduladora de Lactobacillus rhamnosus em macrófagos de camundongos estimulados com Lipopolisacarídeo, Ácido Lipoteicóico e manana - Oliveira, Felipe Eduardo de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Probiotics are able to balance the resident microbiota and modulate the immune response to different microbial stimuli, however its immunomodulatory effects are not clearly understood. This study intends to evaluate the immunomodulatory effect of Lactobacillus rhamnosus or its products on macrophages (RAW 264.7) activated by lipopolysaccharide (LPS), lipoteicoic acid (LTA) or mannan through the analysis of the production of pro and anti-inflammatory cytokines (TNF-α, IL-1 β, IL-4, IL-6, IL-10, IL-12). It was used the standard strain of L. rhamnosus ATCC 7469, seeded on Agar Man-Rogosa-Shape (MRS) and grown at 37°C/5% CO2 for 24 h. Three different preparations of probiotics were prepared: 1) L. rhamnosus solution at a concentration of 5 x 107 cells/mL; 2) Heat-killed L. rhamnosus, obtained by autoclaving previous preparation at 121°C/15 min, 3) Supernatant of L. rhamnosus suspension, obtained through centrifugation of the suspension with heat-killed probiotic at 8300 xg/10 min. Mouse macrophages (RAW 264.7) grown in complete DMEM medium (supplemented with 10% fetal bovine serum) were distributed in polystyrene microplates at a concentration of 1 x 106 viable cells/well/ml complete DMEM medium. After 24 h incubation (37°C/5% CO2) for cell adhesion, plates were washed with sterile-apirogenic physiologic saline and cells were stimulated with Escherichia coli LPS, Enterococcus faecalis LTA or Saccharomyces cerevisiae mannan at a concentration of 1 μg/mL, in the presence or absence of the different preparations of probiotics at the same time for 2,5 h. Then the plates were washed, had its medium traded and were incubated for 16 h (37°C/5% CO2). Culture supernatants were 14 collected for the detection and quantification of cytokines (TNF-α, IL-1β, IL-4, IL-6, IL-10 and IL-12) by ELISA immunoenzymatic method. The results were statistically analyzed by ANOVA and Tukey tests (p≤0,05). With ...

Os probióticos são capazes de equilibrar a microbiota residente e modular a resposta imune aos diferentes estímulos microbianos, entretanto, seus efeitos imunomoduladores ainda não estão claramente elucidados. O presente estudo avaliou o efeito imunomodulador de Lactobacillus rhamnosus ou seus produtos sobre macrófagos (RAW 264.7) ativados por lipopolissacarídeo (LPS), ácido lipoteicóico (LTA) ou manana, pela análise da produção de citocinas pró e anti-inflamatórias (TNF-α, IL-1 β, IL-4, IL-6, IL-10, IL-12). Foi utilizada a cepa padrão de L. rhamnosus ATCC 7469, semeada em Ágar Man-Rogosa-Shape (MRS) e cultivada a 37ºC/5% CO2 por 24 h. Foram empregadas três diferentes preparações de probióticos: 1) L. rhamnosus vivo (LV) na concentração de 2,5 x 107 células/mL; 2) L. rhamnosus morto (LM) obtido por autoclavagem da preparação anterior a 121°C/15 min; 3) Sobrenadante da suspensão de L. rhamnosus (SL), resultante da centrifugação da suspensão LM a 8300 xg/10min. Foram utilizados macrófagos de camundongos (RAW 264.7), cultivados em meio DMEM completo (suplementado com 10% de soro fetal bovino) foram distribuídos em microplacas de poliestireno na concentração de 5 x 105 células viáveis/poço/mL de meio DMEM completo. Após 24 h de incubação (37°C/5% CO2) para adesão celular, as placas foram lavadas com PBS estéril e apirogênico e as células foram estimuladas com LPS de Escherichia coli, LTA de Streptococcus faecalis ou manana de Saccharomyces cerevisiae na concentração de 1 μg/mL, na presença ou ausência das diferentes preparações dos probióticos por 2,5h. Em seguida as placas foram lavadas com PBS, tiveram seu meio trocado e foram incubadas por 16h (37°C/5% CO2). Os sobrenadantes das culturas foram coletados para a detecção e quantificação das citocinas (TNF-α, IL-1β, IL-4, IL-6, IL-10 e IL-12) pelo método imunoenzimático ELISA. Os ....
Keywords: Probióticos; Macrofagos; Citocinas